Contemporary Development and Sustainability Indicators at the Royal Commission of Yanbu - A.AlShehai, Ayedh (European Journal of Sustainable Development, 2018)
Contemporary development in the Royal Commission of Yanbu (RCY) relies on the comprehensive set of sustainability indicators which have been developed through forty years of experience and studies. The city was built in 1974, with the concept of sustainable development for the oil and petroleum industries which serves the community with a population of 115,000. Recently, the RC won many international awards in development under the United Nation Development Program (UNDP) which is considered an indicator for positive progress in sustainability. The aim of this paper is to explore twelve sustainability indicators implemented at RCY. The proposed sustainability indicators were contributed by nine divisions. The methodology in selecting indicators in terms of measurable success was crafted through the knowledge of local and international organizations such as UNDP, European Union (EU), and Environment Protection Agency (EPA). The findings show that RCY has predominantly made excellent progress in sustainability by accomplishing the goal of efficiency in resources and materials. There are twelve categories designed for sustainable development at the RCY. It contains a comprehensive set of indicators updated annually. In conclusion: sustainability indicators influence the growth of income and made harmonious between the economies and the community at RCY. Keywords: sustainability indicators, quality of life, sustainability development, harmony, industrial, economy and communities, environment.